1993
DOI: 10.1159/000177761
|View full text |Cite
|
Sign up to set email alerts
|

A High Omega 3 Fatty Acid Diet Alters Fatty Acid Composition of Heart, Liver, Kidney, Adipose Tissue and Skeletal Muscle in Swine

Abstract: The fatty acid profiles and total lipid contents of two skeletal muscles, adipose tissue, heart, liver and kidney of swine fed a diet rich in omega 3 (n-3) fatty acids (i.e., 5% fish oil) was investigated. These values were compared to those determined for animals which were fed an equal caloric diet low in n-3 fatty acids (i.e., 5% coconut oil). All supplementations were given over a 13-week period. The lipids were extracted with chloroform-methanol, transesterified and the relative fatty acid methylesters co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…The dietary treatment in this case had no significant influence on the fatty acid composition of liver fat. However, Otten et al (1993) reported that the fatty acid profile of liver fat is related to the fatty acid pattern of plasma which depends in turn partially on the feeding given. Therefore, the pig liver had little capacity of fatty acid synthesis.…”
Section: Barley As Single Ingredient In Diet For Finishing Pigs 613mentioning
confidence: 99%
“…The dietary treatment in this case had no significant influence on the fatty acid composition of liver fat. However, Otten et al (1993) reported that the fatty acid profile of liver fat is related to the fatty acid pattern of plasma which depends in turn partially on the feeding given. Therefore, the pig liver had little capacity of fatty acid synthesis.…”
Section: Barley As Single Ingredient In Diet For Finishing Pigs 613mentioning
confidence: 99%
“…Tissue fatty acid composition is a dynamic system constantly receiving, oxidizing, and incorporating dietary and de novo synthesized fatty acids. Compared to the adipose tissue, the metabolic turnover in the intramuscular fat is higher [28] and therefore differences in CLA incorporation might also be due to differences in the turnover rate and/or CLA isomers might be discriminated against the synthesis of muscle tissue lipids.…”
Section: Lipogenic Enzyme Activity Lipid Content and Fatty Acid Profmentioning
confidence: 99%
“…Dietary levels of essential fatty acids will have a large effect on the levels of the corresponding fatty acids in adipose tissue, since the dietary fatty acids replace the de novo synthesis of other fatty acids (Wiseman et al 2000). This is particularly true for the essential fatty acids linoleic and linolenic acid (Leat et al 1964;Brooks 1967;Wahlstrom et al 1971;Berschauer 1983;Christensen 1985;Hartman et al 1985;Whittington et al 1986;Phetterplace and Whatkins 1989;Osterballe et al 1990;Ajuyah et al 1991;Vilchez et al 1991;Otten et al 1993;Agunbiade et al 1999). For example, Morgan et al (1992) fed pigs either a diet containing 5% tallow or 5% soya oil to produce diets with large differences in fatty acid profile.…”
mentioning
confidence: 99%